Saving earth : climate change and the fight for our future - Rhuday-Perkovich, Olugbemisola; Foley, Tim, 1962- (2022)
"A timely and important illustrated nonfiction guide for middle grade readers about the history of our fight against climate change, and how young people today can rise to action"--
Includes bibliographical references and index.
Grades 4-6
Keywords: Climatic changes -- Juvenile literature; Green movement -- Juvenile literature